Examining the effect of a Mini Med School using social cognitive career theory - Papp, Kimberly M; Shang, Sam RY; Ross, Shelley (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: Diversity of professionals within the healthcare system enhances patient outcomes. Existing literature indicates that Mini Medical School (MMS) Programs can increase medical school diversity by engaging youth from underrepresented backgrounds (URiM+); however, there is limited understanding of the mechanisms by which this happens. Further research could refine these programs and improve their effectiveness. Grounded in social cognitive career theory, this study evaluates the impact of a single-day MMS on URiM+ students’ knowledge and confidence in pursuing medicine.Methods: Female and gender-diverse youth were invited to urban or rural single-day MMS events organized by medical students. These MMS programs included clinical skills activities and a lecture about becoming a physician. Participants completed a pre- and post-event survey and quiz assessing their interest, knowledge, and confidence in pursuing a medical career.Results: Participants at both MMS events reported increased confidence about pursuing a career in medicine. Both subjective and objective measures of knowledge about a career in medicine increased. Interest in pursuing a career in medicine, however, did not increase significantly in either group. A significant positive correlation was found between participants' self-confidence in becoming a physician and their perceived knowledge of how to become a physician.Conclusions: We found that these single-day MMS programs increased participants’ knowledge about the steps to pursuing a career in medicine, and their confidence in their ability to do so, but did not significantly increase their interest. When considering the impacts of MMS programs from a social cognitive career theory lens, program organizers should consider ensuring that their MMS curriculum includes practical tools for success, as this will contribute to supporting URiM+ students in viewing themselves as future physicians and contributing to the aim of diversifying the medical profession.